Explicit and Implicit Self-esteem and Aggression: Differential Effects of Agency and Communion - Snowden, Robert J. (Journal of interpersonal violence, 2022)
Previous work has shown that self-esteem is related to aggression and violence. However, self-esteem is a multidimensional construct, and so we isolated self-esteem related to agency (e.g., competence and assertiveness) and self-esteem related to communion (e.g., warmth and morality) using both explicit and implicit techniques and examined their relationship to two forms of aggression (proactive and reactive aggression) in two samples. In an undergraduate sample (N = 130), high levels of explicit agency were associated with increased aggression but only for those with low implicit agency. On the other hand, high levels of either explicit or implicit communion showed reduced proactive aggression, while high levels of explicit communion were also associated with low levels of reactive aggression. In a community sample of people with problems due to homelessness (N = 101), we found that high levels of explicit communion were also associated with lower levels of both forms of aggression. The results show that different aspects of self-esteem, namely agency and communion, have quite different relationships to aggression and that implicit measures of these self-evaluations are also important constructs in the prediction of aggression. Implicit measures of self-esteem could be used by clinicians to understand the motivations behind an individual?s aggression and its management.